AN ANALYSIS OF CUSTOMER SHOPPING BEHAVIOR IN AN OUT-OF-STOCK SITUATION: A CASE STUDY AT THE HYPERMARKET GIANT IN PURWAKARTA - Maulana, Andre; Sitepu, Badikenita (Directorate of Academic Research and Community Services, 2020)
Every retailers want to keep their customers from leaving the store. One of the conditions that can make customers leave the store is when they experience out of stock situation. Out of stock is a threat to all retailers, including in Giant Purwakarta. The existence of out of stock conditions can make consumers leave the store or stay in the store. The decision to stay or leave the store is influenced by the characteristics that the consumer have. This study examines how much influence of the customer?s characteristic to the customer response when Giant Purwakarta out of stock. The type of this research is descriptive quantitative by using Pearson Chi-Square formula to analyse the relationship between variables. The results show that there are three characteristics that have significant value with customer response. The three characteristics are: general time constraint, brand loyalty, and store loyalty. On the other hand, the three characteristics of consumers found have no significant value with customer response when Giant Purwakarta facing out of stock. The three irrelevant characteristics are: Store distance, store price, and shopping trip. These results suggest that loyalty and time to shop become the most influential factors on consumer decision making to leave the store or stay in the store when retail store facing out of stock condition.